PERENCANAAN SISTEM DRAINASE PERUMAHAN GRAND KENJERAN DENGAN PRINSIP ZERO DELTA Q - NURUL JANNAH ASID (Program Studi Teknik Sipil Universitas Narotama, 2022)
Grand Kenjeran Residence is a mega project which has a lot of access and facilities at East Surabaya district. Related to the development’s location, East Surabaya District had peat and swamp like soil which has high land subsidence and prone to be flooded. Based on that condition, a drainage system is required to draining the rainwater towards existing drainage system. Zero Delta Q Policy is a “flood caution” concept by applying flood’s runoff restrictions as a result of the development, which the difference between before and after runoff debit has to be zero. Based on the analyzing report, there are some chsnnel precast available to use for Drainage System 1 : Box Culvert size 200x150x100 cm ; Box Culvert size 120x120x100 cm ; Uditch + Cover size 50x50x120 cm and Drainage System 2 : Box Culvert size 120x150x100 cm; Box Culvert size 100x100x100 cm ; Uditch + Cover size 40x50x120 cm. Fulfilling the “Zero Delta Q” concept, the design of boezem had volume of 7.182,47 m3 which is larger than the requirements at 7.181,925 m3 and floodgates on drainage system.